Survey of Hungarian High School Students’ Financial Literacy in the Last 10 Years Based on the Econventio Test - Kovács, Péter; Kuruczleki, Éva; Rácz, Tamás Attila; Lipták, Lilla (Public Finance Quarterly, 2021)
The Econventio Association in cooperation with the Faculty of Economics and Business Administration of the University of Szeged has been developing the financial literacy of high school students since 2011. In our study, we summarize the main findings of surveys over the past 10 years, based on a total of 110,000 responses. Our findings show high school students to have inadequate and superficial financial knowledge. The results show that high school students have low financial literacy levels. Financial knowledge is positively related to long-term oriented thinking, the opinion formed about self-sufficiency and self-care, and the general attitude towards finances. In addition to the everincreasing role of digital financial information sources, high school students draw their financial knowledge mainly from what they see at home, which influences test scores in a negative way, while at the same time financial literacy education has a positive effect on students’ financial literacy. As age and experience increase, the level of financial knowledge increases too, especially in the topics of labour market, credits and loans and insurance, however, the problematic areas remain the same over time, both for high school students and the adult population: calculating interest, compound interest, the meaning of expressions 'at least' or ‘at most’, or comparing different financial offers.